(untitled) (Research, Society and Development, 2022)
Objective: Mapping and contesting knowledge in scientific productions on nursing care for humanized. Method: This was an integrative literature review of an exploratory-descriptive nature and of qualitative origin. Twenty-two articles in Portuguese were selected, related to the study theme. Discussion: it was divided into categories, namely: Practices aimed at better support in nursing care for humanized childbirth; The factors that have hampered the implementation of humanized care in childbirth. Conclusion: That there is better preparation of nursing professionals, through training, workshops, training and periodic meetings and also encourage them to follow the recommendations of the main health agencies in order to provide more humanized care that somehow benefit the woman and the baby, ensuring there are no unnecessary and medicalized procedures.